An adaptive simulation intervention decreases emergency physician physiologic stress while caring for patients during COVID-19: A randomized clinical trial - Leigh V. Evans; James W. Bonz; Samuel Buck; Jeffrey N. Gerwin; Shacelles Bonner; Suzette Ikejiani; Tatiana Moylan; Melissa Joseph; Gustavo de Oliveira Almeida; Jessica M. Ray; James D. Dziura; Arjun K. Venkatesh; et al. (PLoS ONE, 2025)
Background Stressful work environments and burnout in emergency medicine (EM) physicians adversely impact patient care quality. The future EM workforce will need to prioritize clinician well-being to ensure optimal patient care. Methods This prospective, randomized, controlled study aimed to determine whether an adaptive simulation intervention, COVID-19 Responsive Intervention: Systems Improvement Simulations (CRI:SIS), decreased physiologic stress as measured by heart rate variability (HRV) in front-line EM physicians during the COVID-19 pandemic. HRV was measured with smart shirts and self-reported State-Trait Anxiety Inventory (STAI) were collected at baseline and during four 8-hour clinical shifts for all participants. The intervention group (n = 40) received a 3-hour virtual educational simulation intervention consisting of four simulation scenarios (CRI:SIS). The control group (n = 41) received no simulation intervention. Results There were no significant differences in demographics between groups. HRV data collected from 81 physicians across a total of 324 clinical shifts showed an increase in HRV (decrease in physiologic stress) in shifts immediately following CRI:SIS in the intervention group as measured by a root mean square standard deviation (RMSSD) difference of 11.55 ms (95% CI, −19.90 to −3.20; P = 0.007) compared to the control group. Post-intervention STAI did not significantly differ between intervention and control. Conclusion An adaptive simulation-based educational intervention led to decreased physiologic stress (increased HRV) among emergency physicians who received a simulation education intervention. Reduced physiologic stress generated by adaptive simulation interventions may improve both patient safety and clinician well-being.